Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/jvi.05648-11
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Nasopharyngeal Carcinoma Nuclear Proteome Induced by the EBNA1 Protein of Epstein-Barr Virus Reveal Potential Roles for EBNA1 in Metastasis and Oxidative Stress Responses

Abstract: Epstein-Barr virus (EBV) infection is causatively associated with a variety of human cancers, including nasopharyngeal carcinoma (NPC).The only viral nuclear protein expressed in NPC is EBNA1, which can alter cellular properties in ways that may promote oncogenesis. Here, we used 2-dimensional difference gel electrophoresis (2-D DiGE) to profile changes in the nuclear proteome that occur after stable expression of EBNA1 in the EBV-negative NPC cell line CNE2. We found that EBNA1 consistently altered the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 56 publications
(65 reference statements)
0
58
0
Order By: Relevance
“…In addition, EBNA1 was found to increase the expression of the NOX2 NADPH oxidase which might account for the ROS induction (Gruhne et al 2009). Similarly, a comparison of the nuclear proteome in NPC cells with and without EBNA expression showed that EBNA1 increased the levels of several oxidative stress response proteins including the antioxidants superoxide dismutase 1 and peroxiredoxin 1, known to be induced by ROS (Cao et al 2011). Further studies confirmed that, in the presence of EBNA1, ROS levels were elevated and that NOX1 and NOX2 transcripts were increased (Cao et al 2011).…”
Section: Induction Of Oxidative Stressmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, EBNA1 was found to increase the expression of the NOX2 NADPH oxidase which might account for the ROS induction (Gruhne et al 2009). Similarly, a comparison of the nuclear proteome in NPC cells with and without EBNA expression showed that EBNA1 increased the levels of several oxidative stress response proteins including the antioxidants superoxide dismutase 1 and peroxiredoxin 1, known to be induced by ROS (Cao et al 2011). Further studies confirmed that, in the presence of EBNA1, ROS levels were elevated and that NOX1 and NOX2 transcripts were increased (Cao et al 2011).…”
Section: Induction Of Oxidative Stressmentioning
confidence: 72%
“…Similarly, a comparison of the nuclear proteome in NPC cells with and without EBNA expression showed that EBNA1 increased the levels of several oxidative stress response proteins including the antioxidants superoxide dismutase 1 and peroxiredoxin 1, known to be induced by ROS (Cao et al 2011). Further studies confirmed that, in the presence of EBNA1, ROS levels were elevated and that NOX1 and NOX2 transcripts were increased (Cao et al 2011). Therefore, EBNA1 appears to have multiple effects on the oxidative stress response, although the mechanisms of these effects are not yet known.…”
Section: Induction Of Oxidative Stressmentioning
confidence: 97%
“…ROS production is dependent on paracrine secretion of interleukin 10 (IL-10) in latency I, whereas expression of EBV nuclear antigen 2 (EBNA-2) and latent membrane protein 1 (LMP1) is proposed in latency III (66). EBNA-1 could also be involved in ROS production (67,68 carcinoma resulted in an increase in ROS production (69). Taken together, these studies indicated that ROS production induced by EBV could play a role in genome instability as well as in metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EBNA1 counter-acts the stabilization of p53 by USP7 and induces the loss of PML nuclear bodies through the degradation of PML proteins, both of which contribute to the ability of EBNA1 to interfere with apoptosis and DNA repair (20,21). EBNA1 has also been found to inhibit transforming growth factor ␤ and NF-B signaling and to induce oxidative stress (22)(23)(24)(25). EBNA1 may also be able to transactivate the expression of some cellular genes.…”
mentioning
confidence: 99%